Design of a Frequency-Selective Rasorber Based on Notch Structure - Qu, Meijun; Sun, Siyang; Deng, Li; Li, Shufang (IEEE access, 2019)
This paper reports a dual-polarized frequency-selective rasorber that has a transmission window with low insertion loss and two absorption bands at both sides of the passband. Equivalent circuit and simple design guidelines for rasorber design are further developed. First, the notch structure with high Q is used to make the absorber realize the notch characteristic. Then, a frequency selective surface is utilized to replace the ground of the absorber. Note that the center frequency of the passband is consistent with the notch frequency. Therefore, the incident power is allowed to penetrate the proposed rasorber with a low insertion loss and transmissive behavior of the proposed rasorber is realized by this way. In addition, it is found that the main transmission band and lower absorption bands almost maintain stable performances in the angular range of 0° to 35°, while the upper absorption bands get slightly worse as angular range increases for both the TE and TM incidences. A rasorber prototype has been fabricated to experimentally validate the principle and design approach. The measurements agree reasonably with the simulated ones. Finally, a broadband and high-selectivity rasorber is achieved simultaneously.